Diagnostic accuracy of SARS-CoV-2 rapid antigen self-tests in asymptomatic individuals in the omicron period: a cross-sectional study. (March 2023) - Venekamp, Roderick P.; Schuit, Ewoud; Hooft, Lotty; Veldhuijzen, Irene K.; van den Bijllaardt, Wouter; Pas, Suzan D.; Zwart, Vivian F.; Lodder, Esther B.; Hellwich, Marloes; Koppelman, Marco; Molenkamp, Richard; Wijers, Constantijn J.H.; et al.
Abstract: Objectives: To assess the performances of three commonly used antigen rapid diagnostic tests used as self-tests in asymptomatic individuals in the Omicron period. Methods: We performed a cross-sectional diagnostic test accuracy study in the Omicron period in three public health service COVID-19 test sites in the Netherlands, including 3600 asymptomatic individuals aged ≥ 16 years presenting for SARS-CoV-2 testing for any reason except confirmatory testing after a positive self-test. Participants were sampled for RT-PCR (reference test) and received one self-test (either Acon Flowflex [Flowflex], MP Biomedicals (MPBio), or Siemens-Healthineers CLINITEST [CLINITEST]) to perform unsupervised at home. Diagnostic accuracies of each self-test were calculated. Results: Overall sensitivities were 27.5% (95% CI, 21.3–34.3%) for Flowflex, 20.9% (13.9–29.4%) for MPBio, and 25.6% (19.1–33.1%) for CLINITEST. After applying a viral load cut-off (≥5.2 log10 SARS-CoV-2 E-gene copies/mL), sensitivities increased to 48.3% (37.6–59.2%), 37.8% (22.5–55.2%), and 40.0% (29.5–51.2%), respectively. Specificities were >99% for all tests in most analyses. Discussion: The sensitivities of three commonly used SARS-CoV-2 antigen rapid diagnostic tests when used as self-tests in asymptomatic individuals in the Omicron period were very low. Antigen rapid diagnostic test self-testing in asymptomatic individuals may only detect a minority of infections at that point in time. Repeated self-testing in case of a negative self-test is advocated to improve the diagnostic yield, and individuals should be advised to re-test when symptoms develop.